Perioperative management of coagulation - Innerhofer, P. (Hämostaseologie, 2006)
Guidelines of official societies for diagnosis and therapy of intraoperatively occurring hypocoagulability rely mainly on data of patients receiving whole blood transfusions. They recommend -provided that laboratory evaluation shows deficiency (values >1.5 fold normal)- administration of fresh frozen plasma, cryoprecipitate and platelet concentrates (platelet count <50 000 or <100 000/μl). This article describes the pathogenesis of coagulopathy in the light of the special intraoperative setting, emphasizes recent changes of blood component preparation, transfusion triggers, effects of volume therapy and challenges standard laboratory assays as reliable guide for intraoperative hemostatic therapy. The role of thrombelastographic monitoring is discussed as well as an alternative strategy to compensate deficiencies by the use of coagulation factor concentrates instead of or in addition to transfusion of FFP, a new concept which is illustrated by the presentation of an actual case report.
Keywords: Haemostasis; laboratory testing; PT; aPTT; fibrinogen; haemorrhage; volume therapy; thrombelastography/ thrombelastometry; TEG; ROTEM